2019
DOI: 10.1111/jcpp.13105
|View full text |Cite
|
Sign up to set email alerts
|

A video‐based measure to identify autism risk in infancy

Abstract: Background Signs of autism are present in the first 2 years of life, but the average age of diagnosis lags far behind. Instruments that improve detection of autism risk in infancy are needed. This study developed and tested the psychometric properties of a novel video‐based approach to detecting ASD in infancy. Methods A prospective longitudinal study of children at elevated or lower risk for autism spectrum disorder was conducted. Participants were 76 infants with an older sibling with ASD and 37 infants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Ages of the children involved in the studies varied greatly. Two studies involved children from 6 to 18 months [ 42 , 43 ]. Six studies involved children within the 10 to 48 months range [ 36 , 40 , 41 , 44 , 45 , 46 ], seven studies involved participants aged between 16 and 30 months [ 22 , 25 , 31 , 32 , 34 , 35 , 47 ], and four studies involved children within the 18- and 72-months range [ 37 , 39 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ages of the children involved in the studies varied greatly. Two studies involved children from 6 to 18 months [ 42 , 43 ]. Six studies involved children within the 10 to 48 months range [ 36 , 40 , 41 , 44 , 45 , 46 ], seven studies involved participants aged between 16 and 30 months [ 22 , 25 , 31 , 32 , 34 , 35 , 47 ], and four studies involved children within the 18- and 72-months range [ 37 , 39 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a similar vein, the studies reported by Egger et al [ 25 ] and Carpenter et al [ 36 ] were included both in the NUI and PC/Mobile category. Accordingly, 11 papers reported on the use of computerized solutions (PC or mobile platforms) to administer parent-reported questionnaires [ 22 , 31 , 32 , 33 , 34 , 35 , 37 , 39 , 46 , 47 , 55 ], and seven papers employed screening tools in which videos were collected from [ 37 , 39 , 43 , 50 ] or showed via [ 25 , 36 , 42 ] parents’ mobile/PC devices.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The timing of expression of ASD susceptibility genes during fetal development is in line with the early detection of core symptoms in individuals with ASD. Although the age at which ASD behavioral traits emerge varies, many of the signs, such as gaze aversion, are detectable by as early as 12 months [16,17]. That early brain developmental deficits underlie ASD is further supported by postmortem studies of ASD brains which reveal cortical deficits explainable by alterations in prenatal development [18].…”
Section: Introductionmentioning
confidence: 95%